Step kinematic predictors of short sprint performance in field sport athletes - Lockie, R.; Murphy, A. J.; Jeffriess, M. D.; Callaghan, S. J. (Serbian Journal of Sports Sciences, 2013)
Field sport athletes must generate high velocities over short distances (10 meters [m] or less). The interaction between step kinematics (step length, step frequency, contact time, flight time) determines sprint velocity. This study determined the step kinematics that predicted 10-m sprint performance (0-5, 5-10, 0-10 m intervals) through stepwise multiple regression (p </= 0.05). Spearman`s correlations (p </= 0.05) were also conducted between step kinematics and velocity for each interval. 0-5 m step length and 0-10 m contact time predicted 0-5 m velocity (R = 0.685; p = 0.006). 0-5 m contact time, and 5-10 m step length and step frequency predicted 5-10 m velocity (R = 0.715; p = 0.002). 5-10 m step length and step frequency predicted 0-10 m velocity (R = 0.606; p = 0.001). Correlations were found between 0-5 m velocity and step length in all intervals, and 0-5 m flight time (? = 0.406-0.515; p = 0.011-0.045). 0-10 m velocity correlated with 5-10 and 0-10 m step length, and 0-5 m flight time (? = 0.398-0.444; p = 0.026-0.048). Longer step lengths were integral for short sprint speed in field sport athletes. Step length should be developed in these athletes to improve short distance velocities.